Analysis Of Profitability Ratio And Macroeconomic Factors To Stock Return And Swot Strategy (case Study: Mining Sector Companies Listed In Indonesian Stock Exhange Year 2010-2014) - Emeral Sakinah; Endang Chumaidiyah; Rita Zulbetti (eProceedings of Engineering, 2016)
Capital markets have an important role for the economy of a country because capital markets serve two functions, namely a means for companies to get funds and facilities for the community to invest in financial instruments. The fall in stock returns in the mining sector listed in Indonesia Stock Exchange 2010-2014 period behind this research, because stock returns tend to decline would be detrimental to the shareholders. This study aims to determine the effect of profitability as measured by net profit margin and earnings per share and macro economic factor which measured by inflation on stock returns and provide strategic recommendations for companies that have a return value low in order to improve the return the company back, method used is the method descriptive. The analysis used is multiple linear regression hypothesis testing using the F and T test. After doing research, it is obtained results showed that the profitability as measured by net profit margin and earnings per share and also the macroeconomic as measured by inflation on stock returns. The effect of profitability and macroeconomic factors of the stock return is 38.9%. Based on analysis of strength, weakness, opportunity and threat of PT Bumi Resources Tbk as representative company in mining sector, the position of the company is in Quadrant II which is the proper strategy that can be used is S-T strategy. S-T strategy means company needs to maximize strength and avoid threat. Keywords: Profitability Ratio, Stock Return, SWOT Analysis